Yoni dip también tiene hambre o el silencio de las tripas - Garzón Vélez, Julián (2023)
This dramatic text addresses the issue of homelessness from the human sensibility. It explores social injustice, famine, homelessness, lack of opportunities and love as the driving force of the family. It questions meritocracy as the only vision of progress and brings, from the metaphor, the hope of change through personal transformation. It opens a window into the lives of people who end up living on the streets due to different circumstances and raises questions about the social and human responsibility we all have towards each other. This work is the result of a research on social injustice and inequality. It gathers real cases, documents, fragments and life stories of situations of poverty, which are framed in the theme of hunger and the analogical relationship between the human and the dog's life. Thus, although for many the dog means fidelity and companionship, it is also synonymous of being adrift, of being a stray dog, being treated badly and living, as popular sayings state, a dog's life.